Obtención de snack alimenticio a partir de cuatro variedades de papa (Solanum tuberosum L), utilizando aceites esenciales de rizomas - Toapanta Guzman, Doris Emilia (2024)
The objective of the research was to obtain a food snack from four varieties of potato (solanum tuberosum), using essential oils from rhizomes. A bibliographic review of the raw material, extraction methods, steam distillation and essential oil quality criteria was carried out. The raw material was obtained from the central and northern zone of Guaranda Canton because of its nutritional value, agroindustrial management and commercialization. An AxB (2x2) factorial design was applied. The response variables evaluated for the oil were volume yield, density, and antioxidant activity. In relation to the essential oil, the best treatment for volume yield was T4. In density the best treatment was T2 and in antioxidant activity the best treatment was T3-T4. The response variables for the snack were sensory analysis and antioxidant activity. The ABTS technique was used to determine the main antioxidant components. To determine the quality of the essential oil, the density and refractive index were determined, obtaining a density of 0.87g/ml for ginger essential oil and 0.92g/ml for turmeric essential oil, indicating that the lower the density of the essential oil, the better the quality; the refractive index was 1.49nD for ginger essential oil and 1.5nD for turmeric essential oil, which shows the purity of the essential oil.